Power market and derivatives - Dúbravský, Martin (2019)
Commodities used on worldwide scale and daily basis, are also traded on their separate markets. Electric power in Germany, is no excetion in this regard. Apart from description of characteristics of electric power, this thesis analyze derivative products on electricity in Germany traded on EEX. Ex -post futures risk premium is analyzed using approaches proposed by Bessembinder & Lemmon (2002) and Fama & French (1987). Bessembinder's approach is build on theory of hedging pressure. Risk premium is expected to rise with skewness of spot price during delivery of futures and decrease with increasing variance. Results show exactly opposite tendency. Reason for this might be one of the assumption of the model, that futures market provides insurance, rather than speculation. It was shown that regardless of month of delivery, basis contains information about developement of spot price between delivery period and present. Moreover, basis provides information about level of risk premium for deliveries of 5th-7th month and from 10th-12th. Principal components analysis of EEX forward curve was performed and it was found, that significant dimension reduction is possible without loss of any major information content in forward curve. Dominant components and their shapes were discussed in both short-term and long-term delivery horizons. Dominant movements of long-term deliveries futures are explained by coal-phaseout and structural change of German merit-order. Options on front-month futures deliveries were studied, utilizing well known Black-Scholes-Merton model. Implied volatility and its term structure were analyzed and it was shown, that due to mean-reverting nature of underlying asset, level of implied volatility is increasing as time approaches exercise date. It was also shown, that implied skew of volatility is increasing as time approaches expiry date. Seasonal pattern of this phenomena was also shown to be significant.